(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Determine and compare the satisfaction levels of nursing students with online and face-to-face learning during the New Normal in The Era of Pandemic COVID-19. Methods: A cross-sectional study using a structured questionnaire assessed nursing students’ opinions regarding their courses, including second and third-year students. Results: Students are delighted with face-to-face learning during the New Normal in the Era of the COVID-19 pandemic. Furthermore, they find this method more satisfactory than online learning, and the difference is statistically significant. Conclusions: Enhancing teaching methods and approaches is essential to improving the quality of training and effectively responding to future emergency epidemic situations.